Time of Emergence of Permanent Teeth and Impact of Nutritional Status among 4-15 Years Old Children and Teenagers in Basrah City /Iraq - Ahmed, Hiyam S.; Al-Dahan, Zeyneb A. (Journal of Baghdad College of Dentistry, 2016)
Background: The timing of eruption of permanent teeth is of considerable importance to the dental health planning for diagnostic, preventive and therapeutic measures for children and teenagers. The purposes of this study were to determine timing of maxillary and mandibular permanent teeth emergence (except third molars) and to evaluate the effect nutritional status by anthropometric measures on the eruption time of permanent teeth, investigations had been done according to jaw and gender variations.Materials and Methods: This study was conducted among four to fifteen years old children and teenagers from kindergarten and schools in Basrah city in the south region of Iraq. The total sample composed of 1807 children and teenagers that were collected randomly from kindergartens, primary and secondary schools in Basrah city. The data were statistically analyzed by using probit model in order to compute the median 5th and 95th percentile range of emergence. Athropmetric measures of height and weight were used for the purpose of assessment of nutritional status. The indices include: Weight for age, Height for age and Weight for height; each was considered as in term of standard deviation score (Z – score) as primary indicator of underweight, stunting and wasting respectively. The statistical significance of differences in mean of a normally distributed variable (nutritional indices z score) between 2 groups was assessed by independent samples t-test.Results: The results showed significant differences (p